Habituation of reflexive and motivated behavior in mice with deficient BK channel function - Typlt, Marei; Mirkowski, Magdalena; Azzopardi, Erin; Ruth, Peter; Pilz, Peter K.; Schmid, Susanne (Frontiers in Integrative Neuroscience, 2013)
Habituation is considered the most basic form of learning. It describes the decrease of a behavioral response to a repeated non-threatening sensory stimulus and therefore provides an important sensory filtering mechanism. While some neuronal pathways mediating habituation are well described, underlying cellular/molecular mechanisms are not yet fully understood. In general, there is an agreement that short-term and long-term habituation are based on different mechanisms. Historically, a distinction has also been made between habituation of motivated versus reflexive behavior. In recent studies in invertebrates the large conductance voltage- and calcium-activated potassium (BK) channel has been implicated to be a key player in habituation by regulating synaptic transmission. Here, we tested mice deficient for the pore forming α-subunit of the BK channel for short-term and long-term habituation of the acoustic startle reflex (reflexive behavior) and of the exploratory locomotor behavior in the open field box (motivated behavior). Short-term habituation of startle was completely abolished in the BK knock-out mice, whereas neither long-term habituation of startle nor habituation of motivated behavior was affected by the BK deficiency. Our results support a highly preserved mechanism for short-term habituation of startle across species that is distinct from long-term habituation mechanisms. It also supports the notion that there are different mechanisms underlying habituation of motivated behavior versus reflexive behavior.